2016
DOI: 10.3168/jds.2016-11180
|View full text |Cite
|
Sign up to set email alerts
|

Natural lactic acid bacteria population of tropical grasses and their fermentation factor analysis of silage prepared with cellulase and inoculant

Abstract: Natural lactic acid bacteria (LAB) populations in tropical grasses and their fermentation characteristics on silage prepared with cellulase enzyme and LAB inoculants were studied. A commercial inoculant Lactobacillus plantarum Chikuso 1 (CH), a local selected strain Lactobacillus casei TH14 (TH14), and 2 cellulases, Acremonium cellulase (AC) and Maicelase (MC; Meiji Seika Pharma Co. Ltd., Tokyo, Japan), were used as additives to silage preparation with fresh and wilted (6 h) Guinea grass and Napier grass. Sila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 14 publications
(27 reference statements)
8
79
3
4
Order By: Relevance
“…Therefore, the addition of ENZ may not have beneficial effects on promoting the propagation of LAB. Previous studies, have suggested that addition of cellulase could improve the fermentation quality by degrading NDF and ADF of tropical crop and by-product silages (Khota et al 2016;Li et al 2017;Wang et al 2019). This result was not evident in our study, this could be attributed to the fibrolytic enzyme activity which depends on the temperature and pH condition (Colombatto et al 2004).…”
Section: Fermentation Quality and Nutritive Valuecontrasting
confidence: 78%
See 1 more Smart Citation
“…Therefore, the addition of ENZ may not have beneficial effects on promoting the propagation of LAB. Previous studies, have suggested that addition of cellulase could improve the fermentation quality by degrading NDF and ADF of tropical crop and by-product silages (Khota et al 2016;Li et al 2017;Wang et al 2019). This result was not evident in our study, this could be attributed to the fibrolytic enzyme activity which depends on the temperature and pH condition (Colombatto et al 2004).…”
Section: Fermentation Quality and Nutritive Valuecontrasting
confidence: 78%
“…Indeed, enzymes such as xylanases and cellulases, can convert (hemi) cellulose into sugars (Stokes 1992) thereby rendering substrate available for fermentation. In line with this notion, it seems plausible that fibrolytic enzymes can also be applied in the process of ensiling and several authors (Sun et al 2012;Khota et al 2016;Desta et al 2016) have already reported about the potency of fibrolytic enzymes to improve the quality of silage.…”
Section: Introductionmentioning
confidence: 84%
“…The liberation of additional soluble sugars caused by fiber hydrolysis is likely to increase both the rate and extent of lactic acid production. In addition, this process may potentially enhance dry matter intake and ruminal digestibility of alfalfa silages (Sun et al 2009;Khota et al 2016). However, these positive results are not consistent in previous studies assessing cellulase treated alfalfa silages (Kozelov et al 2008;Muck et al 2018), possibly due to the selectivity of cellulases for specific fibre components (high lignin concentration) of certain lucerne materials (Wilson et al 1994).…”
Section: Introductionmentioning
confidence: 61%
“…Previous studies have shown alfalfa is difficult to be ensiled, due to its low WSC and high buffering capacity. Cellulase and LAB have been widely used to improve silage fermentation and enhance the in vitro digestibility in many silage materials (McDonald et al 1991;Santos et al 2013;Khota et al 2016). In silage fermentation studies, the application of cellulase is often included to enhance fiber degradation, providing LAB with more fermentable substrate (McDonald et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Molasses is rich in sucrose, glucose and fructose, which are substrates for LAB during silage fermentation . Cellulase degrades the cell walls (or cellulose) of the silage material and releases available substrates for fermentation by LAB (Tengerdy et al 1991;Khota et al 2016). However, very little information is available on preparing KZ silage with these additives.…”
Section: Introductionmentioning
confidence: 99%